Academic Technology Experience and Preference on Online Learning in Indonesian Higher Education Institutions: Students' Perspectives - Yulian, Ryani; Ruhama', Ufi (Jurnal Pendidikan dan Pengajaran, 2021)
Amidst the Covid-19 Pandemic, most higher education institutions have shifted to online learning to sustain the existence of the universities. However, the readiness and effectiveness of private higher education institutions in Indonesia, especially in Kalimantan, are still questionable. This study focused on analysing and understanding the academic technology experience and preference for online learning in Indonesian higher education institutions from the students' perspectives. A survey of 302 respondents from private higher education institutions was corroborated with semi-structured interviews. The results indicated that the majority of the respondents have limited access to technology devices and ownership. Most of them need academic features integrated into the learning management system for their successful study. The majority of the respondents preferred to have a face-to-face class, but they are receptive to online learning. However, they need to get situated in academic situations that facilitate their technology literacies and skills. In addition, the institutions and lecturers should go in the same direction. Therefore, the data sources can contribute meaningful insights for policy-makers to design accessible and adaptive online learning for the students.